LEGALITAS KESAKSIAN TESTIMONIUM DE AUDITU DALAM PEMBUKTIAN TINDAK PIDANA PENCABULAN ANAK - Wardani, Riska Putri; Kurniawan, Itok Dwi (Sebelas Maret University, 2024)
This article analyzes the value and strength of evidence in the use of testimonium de audituwitnesses in proving the crime of child molestation. Basically, in the KUHAP regulates witnesses and witnessstatements, namely that the information given by a witness in a trial must be information that he heard,saw and experienced himself. The purpose of this article is to prove whether the Pelalawan District Courtdecision Number 44/Pid.Sus/2021/Pn Plw is in accordance with the provisions of criminal procedural law.The research method used is doctrinal or normative legal research. This research is descriptive and applied.The method for collecting legal materials is by means of literature study and the legal materials used areprimary legal materials and secondary legal materials.